Enhanced Performance of In(Ga)As QD Based Optoelectronic Devices through Improved Interface Quality between QD and Matrix Material. Issue 11 (21st June 2019) - Panda, Debiprasad; Chatterjee, Arka; Saha, Jhuma; Das, Debabrata; Singh, Sandeep Madhusudan; Pal, Samir Kumar; Chakrabarti, Subhananda
Abstract : The interface quality in InAs/GaAs and In0.5 Ga0.5 As/GaAs quantum dot (QD) heterostructures are elucidated through the phonon‐assisted vibrational modes and is found better in the latter case. The strain‐induced formation of interface defects and lattice deformations in each self‐assembled QDs have been analyzed by means of room temperature Raman spectroscopy (RS). This study provides an insight into the inter‐dot migration and thermalization process of carriers in both QD families with the aid of steady‐state and time‐resolved photoluminescence (TRPL) measurements. The longer‐wavelength PL peak observed for InGaAs QD demonstrates the maximum strain‐relaxation, thereby facilitating the formation of larger coherent QDs with higher In‐content, lower interface defects and lower optical bandgap. Moreover, formation of smoother interface during the growth of self‐assembled QDs in InGaAs‐based photodetector and solar cell would open up the possibility of narrower spectral response and enhanced light harvesting in infrared regime. Abstract : A detailed investigation regarding Stranski–Krastanov grown InAs and In0.5 Ga0.5 As quantum dots (QDs) is carried out. This study ascertains the cause of larger QD formation and better interface quality in case of In0.5 Ga0.5 As QD compared to the InAs QD. Hence, heterostructures with In0.5 Ga0.5 As QDs are useful for light‐emitting diode and laser applications.